2021
DOI: 10.3389/fphar.2021.683818
|View full text |Cite
|
Sign up to set email alerts
|

Arbutin Ameliorates Murine Colitis by Inhibiting JAK2 Signaling Pathway

Abstract: Background and objective: Abnormal activation of Janus kinase 2 (JAK2) promotes the pathogenesis and progress of inflammatory bowel disease (IBD) by stimulating the cytokine traffic. Based on docking studies, arbutin, a natural product extracted from a traditional medicinal plant bearberry, was found to bind to JAK2. The study aimed to investigate the effects and mechanisms of regulating JAK2 by arbutin on colitis in mice.Methods: A mice colitis model was established to mimic human IBD. The mice freely drank w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Targeted blocking of STAT3 has emerged as a potential therapeutic strategy for alleviating UC. 23 , 33 , 58 Consistent with these findings, our bioinformatics analysis also revealed that the JAK/STAT signaling pathway plays a crucial role in UC. Based on these insights, we examined the expression of phosphorylated STAT3 and the localization of STAT3 within and outside the nucleus before and after HCA treatment in LPS-induced inflammatory FHC cells as well as STAT3 phosphorylation levels in the colonic tissues of mice treated with DSS to investigate whether HCA affects the activation of STAT3.…”
Section: Discussionsupporting
confidence: 82%
“…Targeted blocking of STAT3 has emerged as a potential therapeutic strategy for alleviating UC. 23 , 33 , 58 Consistent with these findings, our bioinformatics analysis also revealed that the JAK/STAT signaling pathway plays a crucial role in UC. Based on these insights, we examined the expression of phosphorylated STAT3 and the localization of STAT3 within and outside the nucleus before and after HCA treatment in LPS-induced inflammatory FHC cells as well as STAT3 phosphorylation levels in the colonic tissues of mice treated with DSS to investigate whether HCA affects the activation of STAT3.…”
Section: Discussionsupporting
confidence: 82%
“…Drugs targeting these cytokines or antibodies have exhibited therapeutic effects on IBD ( 7 , 12 , 55 ); thus, these cytokines are widely accepted as markers of UC. DSS-induced inflammation has previously been shown to be associated with the elevated production of IL-6, IL-18 and IFN-γ, and it could be attenuated in the absence of IL-6, IL-18 or IFN-γ ( 56 ). Therefore, this model is widely accepted for the analysis of the influence of any given drug or compound on the promotion of epithelial cell repair and attenuation of production of inflammatory mediators in animals with UC ( 50 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that C-reactive protein, adherent molecules, and inflammatory cytokines are overexpressed in patients with IBD ( 44 46 ); these chronic inflammatory factors contribute to vascular endothelial dysfunction, carotid intimal thickening, and abnormal carotid atherosclerosis, all of which eventually lead to stroke ( 47 49 ). Second, the destruction of the normal intestinal microenvironment may aggravate this kind of inflammatory reaction ( 50 , 51 ); due to intestinal absorption dysfunction, insufficient absorption of vitamin B6 can lead to an increase in homocysteine, which can also promote the occurrence of stroke ( 52 54 ). Third, our study shows that the incidence of stroke in women is higher than that in men (women: RR = 1.30, 95%CI, 1.18–1.42; men: RR = 1.12, 95%CI, 1.06–1.19), which is contrary to our traditional view.…”
Section: Discussionmentioning
confidence: 99%